UPLC-MS-based serum metabolomics reveals protective effect of Ganoderma lucidum polysaccharide on ionizing radiation injury. (10th August 2020) - Yu, Chunmiao; Fu, Jiaqi; Guo, Lidong; Lian, Lian; Yu, Donghua
Abstract: Ethnopharmacological relevance: Ganoderma lucidum Polysaccharide (GLP), traditional Chinese medicine (TCM) active ingredient, has a long history and has good curative effects on radiation injury. However, the mechanism of GLP treating radiation injury has not been clearly elucidated. The aim of the study: This study was aimed to investigate the preventive effects of GLP on mice with radiation injury and to explore its mechanisms by serum metabolomics. Materials and methods: Thirty mice were randomly divided into three groups, and namely 10 per group. The normal control group and the radiation model with normal saline and GLP group with GLP treatment (96 mg·kg-1) for 14 days. 2 h after 7th day after the intragastric administration, the model group and GLP group were subjected to whole body irradiation by X-rays except the normal control group. The peripheral blood WBC, RBC, HGB, PLT indicators.UPLC-Q-TOF-MS technique was used to analyze the serum of normal group, model group and GLP group, and to explore its potential key biomarkers and corresponding related metabolic pathways. Results: The number of peripheral blood leukocytes (WBC) in the radiation model group was lower than that in the GLP group and the number of platelets (PLT) in the GLP group was significantly higher than that in the model group.Combined with the methods of principal component analysis (PCA), projection to latent structure-discrimination analysis (PLS-DA), three group were clearly distinguished from each other and 18 metabolites were identified as the potential biomarkers in the GLP treated mice. The identified biomarkers indicated that there were perturbations of the taurine and hypotaurine metabolism and glycerophospholipid metabolism. Conclusion: GLP can play a role in radiation protection by improving the expression of related potential biomarkers and related metabolic pathways in serum of radiation-induced mice. Graphical abstract: Image 1